2010
DOI: 10.1071/rj09037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impacts of feral camels

Abstract: Feral camels have significant negative impacts on the environment and the social/cultural values of Aboriginal people. These impacts include damage to vegetation through feeding behaviour and trampling; suppression of recruitment in some plant species; damage to wetlands through fouling, trampling, and sedimentation; competition with native animals for food, water and shelter; damage to sites such as waterholes, that have cultural significance to Aboriginal people; destruction of bushfood resources; reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In addition, the success of feral camels and deer in Australia has been largely attributed to their ability to utilize native trees and shrubs rarely touched by extant macropodoids (Duncan 1992;Edwards et al 2010). There still appears to be a considerable amount of potential browse vegetation, evinced by the number of mixed feeders that consume browse to varying degrees, as well as other browsing taxa such as possums and emus.…”
Section: Dental Morphologymentioning
confidence: 99%
“…In addition, the success of feral camels and deer in Australia has been largely attributed to their ability to utilize native trees and shrubs rarely touched by extant macropodoids (Duncan 1992;Edwards et al 2010). There still appears to be a considerable amount of potential browse vegetation, evinced by the number of mixed feeders that consume browse to varying degrees, as well as other browsing taxa such as possums and emus.…”
Section: Dental Morphologymentioning
confidence: 99%
“…As described above, most studies (e.g. Edwards et al, 2010) report that these impacts are density dependent.…”
Section: Camels and Weedsmentioning
confidence: 99%
“…Although flexible, camels will preferentially eat particular species, including to the point of damage, defoliation and suppression of germinating seedlings (Dorges and Heuke, 2003). As discussed by Edwards et al (2010) in areas of central Australia several studies have demonstrated that camels contribute to local decline of particular plants; in some cases this might conveniently include species deemed undesirable, but it may also include plants such as Quandong and native apricot, which are culturally important for Aboriginal people (Dorges and Heuke, 2003). As described above, most studies (e.g.…”
Section: Camels and Weedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edwards et al (2010) have found that feral camels impose an annual net cost of $10.67 million on the Australian economy and note that the non-market impacts are likely to be significantly higher. Vaarzon-Morel (2010) notes the impacts on natural and cultural resources which are important to Aboriginal people.…”
Section: Impacts and Attitudes Of Land Managersmentioning
confidence: 99%